Effect of Beverages on the Hardness and Tensile Bond Strength of Temporary Acrylic Soft Liners to Acrylic Resin Denture Base - Safari, A (Shiraz University of Medical Sciences, 2013)
Statement of Problem: Two potential problems commonly identified with a denture base incorporating a resilient liner are failure of the bond between acrylic resin and soft liner material, and loss of resiliency of the soft liner over time. Since patients may drink different beverages, it is important to evaluate their effects on physical properties of soft lining materials. Purpose: The objective of this in vitro study was to evaluate the effect of different beverages on the hardness of two temporary acrylic-based soft lining materials and their bond strength to the denture base resin. Materials and Method: For the hardness test; a total of 80 rectangular specimens (40mm×10mm×3mm) were fabricated from a heat-polymerized polymethylmethacrylate. Two commercially auto-polymerized acrylic resin-based resilient liners; Coe-Soft and Visco-gel were prepared according to the manufacturers’ instructions and applied on the specimens. For the tensile test, 160 cylindrical specimens (30mm×10mm) were prepared. The liners were added between specimens with a thickness of 3 mm. The specimens of both soft liners were divided into 4 groups (n=10) and immersed in distilled water as the control group, Coca-Cola, 8% and 50% ethanol. All groups were stored in separate containers at 37(o)C for 12 days. All beverages were changed daily. The hardness was determined using a Shore A durometer and tensile bond strength was determined in a ZwickRoell testing machine at a cross-head speed of 5mm/min. The results were analyzed using two-way ANOVA. Results: There was no significant interaction between the soft liners and the drinks for both hardness (p= 0.748) and bond strength (p= 0.902). There were statistically significant differences between all drinks for both hardness (p< 0.001) and bond strength (p< 0.05). Conclusion: Within the limitations of this study, it seems that drinking Coca-Cola and alcoholic beverages would not be potentially causing any problems for the temporary acrylic soft liners.